2015
DOI: 10.1186/s40643-015-0043-y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of silver nanoparticles using seed exudates of Sinapis arvensis as a novel bioresource, and evaluation of their antifungal activity

Abstract: Background: In general, silver nanoparticles (AgNPs) are particles of silver with a size less than 100 nm. In recent years, synthesis of nanoparticles using plant extract has gained much interest in nanobiotechnology. In this concern, this study investigates green synthesis of AgNPs from silver nitrate using Sinapis arvensis as a novel bioresource of cost-effective nonhazardous reducing and stabilizing compounds. A stock solution of silver nitrate (0.1 M) was prepared. Different concentrations of silver nitrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(56 citation statements)
references
References 31 publications
5
51
0
Order By: Relevance
“…The same pattern were also published for Ag°nanoparticles synthesized from Phanerochaete chrysosporium (MTCC 787/ATCC 24725) culture (Vigneshwaran et al 2006), Schizophyllum radiatum HE 863742.1 (Metuku et al 2014), or from Aspergillus fumigatus (Bhainsa and D'Souza, 2006) following the Joint Plant sources such as Annona squamosa leaf broth (Arjunan et al 2012) produced only Ag o nanoparticles, the same was observed in the case of biogenic synthesis of Ag°nanoparticles from aqueous extract of Gloriosa superba Linn. (Glory Lily) (Ashokkumar et al 2013), Dioscorea bulbifera (Ghosh et al 2012), Sinapis arvensis seeds (Khatami et al 2015), gum tragacanth exudate of the bark from Astragalus gummifer (Fabaceae family) (Kora and Arunachalam, 2012), Gum ghatti from Anogeissus latifolia , Medicago sativa seed exudates (Lukman et al 2011), from Cinnamomum zeylanicum bark extract (Sathishkumar et al 2009), from extract of Lawsonia inermis (Henna) (Gupta et al 2014), and from latex of Jatropha curcas (Bar et al 2009). …”
Section: Biogenic Synthesis Of Ag°nanoparticlesmentioning
confidence: 99%
“…The same pattern were also published for Ag°nanoparticles synthesized from Phanerochaete chrysosporium (MTCC 787/ATCC 24725) culture (Vigneshwaran et al 2006), Schizophyllum radiatum HE 863742.1 (Metuku et al 2014), or from Aspergillus fumigatus (Bhainsa and D'Souza, 2006) following the Joint Plant sources such as Annona squamosa leaf broth (Arjunan et al 2012) produced only Ag o nanoparticles, the same was observed in the case of biogenic synthesis of Ag°nanoparticles from aqueous extract of Gloriosa superba Linn. (Glory Lily) (Ashokkumar et al 2013), Dioscorea bulbifera (Ghosh et al 2012), Sinapis arvensis seeds (Khatami et al 2015), gum tragacanth exudate of the bark from Astragalus gummifer (Fabaceae family) (Kora and Arunachalam, 2012), Gum ghatti from Anogeissus latifolia , Medicago sativa seed exudates (Lukman et al 2011), from Cinnamomum zeylanicum bark extract (Sathishkumar et al 2009), from extract of Lawsonia inermis (Henna) (Gupta et al 2014), and from latex of Jatropha curcas (Bar et al 2009). …”
Section: Biogenic Synthesis Of Ag°nanoparticlesmentioning
confidence: 99%
“…The peak that appeared around 2921 cm −1 is related to the stretching of the C-H bonds [37]. The peak at around 1600 cm −1 was assigned to the amide I bonds (NH) of proteins.…”
Section: Fourier Transform Infrared Spectroscopy (Ftir)mentioning
confidence: 99%
“…Nanomaterials could even be used to control the release of the fertilizer such that the nutrients are only taken up by the plants and not lost to unintended targets like soil, water, or microbes. Recent reports indicated that biosynthesized silver nanoparticles using seed exudates of Spinosa arvensis showed antifungal (Neofusicoccum parvum) activities (Khatami et al 2015) and may be responsible for increased seed germination.…”
Section: Introductionmentioning
confidence: 99%